Adoption determinants of exotic rice cultivars in Bangladesh - Sarkar, Abdur Rouf; Rahman, Mohammad Chhiddikur; Rahaman, Shajedur; Sarker, Mou Rani; Islam, Mohammad Ariful; Balie, Jean; Kabir, Shahjahan (Frontiers Media, 2022)
Agrarian Bangladesh relies heavily on rice. Since independence, many varieties have been released and targeted to increase productivity, farmers' income, and food security. However, few gained widespread adoption. Moreover, farmers in the border regions are adopting exotic cultivars, and it's gradually spreading throughout the country. But, the reasons for adopting exotic rice cultivars are still unexplored. Using field data from 1,260 farm households and 42 focus group discussions, this study analyzes farmers' preferences for domestic and exotic rice varieties and identifies the factors of adoption linked to design national breeding programs and farmers' welfare. Findings show, exotic varieties (69%) monopolized the area coverage in the dry season, whereas in the wet season, domestic varieties (58%) dominated. Farmers select exotic varieties for their better yield and price, low production costs, high grain quality, resistance to pests and diseases, and ability to withstand stresses. Risk analysis shows domestic varieties adoption is riskier with lower returns. The empirical findings indicate that household characteristics, access to institutions and infrastructure, varietal characteristics, and weather condition, all play a significant role in adoption decisions. National breeding should focus on developing rice varieties in response to market demands and farmer preferences toward sustainable food security in Bangladesh.